SISTEM INFORMASI PENGELOLAAN KEUANGAN DI KANTOR CAMAT KECAMATAN BABAT TOMAN - Dea Okta Viani; Choiriyah Choiriyah (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2021)
A financial information system is an information system designed to provide information about money options for users throughout the company. The financial information system is part of the MIS which is used to solve corporate financial problems. In general, the financial information system has an income system consisting of a data processing subsystem supported by an internal audit subsystem that provides internal data and information. For large companies it usually has staff internal auditors. Like other subsystems, this system is also equipped with the financial intelligence subsystem, which collects information from the environment.